SHORT-TERM BLOOD PRESSURE VARIABILITY PREDICTS CARDIOVASCULAR EVENTS AND ALL-CAUSE MORTALITY IN HEMODIALYSIS PATIENTS. (June 2018) - Sarafidis, P.A.; Loutradis, C.; Karpetas, A.; Papadopoulou, E.; Tzanis, G.; Bikos, A.; Raptis, V.; Syrgkanis, C.; Liakopoulos, V.; Papagianni, A.; Bakris, G.; Parati, G.
Abstract : Objective: Long-term office BP variability in hemodialysis patients is associated with increased risk of cardiovascular events and mortality. However, the association of the main hemodynamic culprit in dialysis, i.e. interdialytic BP fluctuations, with outcomes has not been investigated. This study examines the prognostic role of short-term BP variability (BPV) for cardiovascular events and all-cause mortality in this population. Design and method: 227 hemodialysis patients underwent 44hour ambulatory monitoring during a standard interval and followed-up for 30.17 ± 17.70 months. We calculated standard deviation (SD), weighted SD (wSD), coefficient of variation (CV), and average real variability (ARV) of BP with validated formulas. The primary end-point was first occurrence of all-cause death, non-fatal myocardial infarction or non-fatal stroke. Secondary end-points were: (i)all-cause mortality; (ii)cardiovascular mortality; (iii)a combination of cardiovascular death, non-fatal myocardial infarction, non-fatal stroke, resuscitation after cardiac arrest, coronary revascularization or hospitalization for heart failure. Results: Cumulative freedom from the primary end-point was similar for quartiles of predialysis SBP and 44hour-SBP, but was progressively longer for increasing quartiles of 44hour-SBP-SD (p = 0.014), wSD (p = 0.007), CV (p = 0.031) and ARV (83.9%, 71.9%, 70.2% and 43.9% for quartiles 1 to 4 respectively; p < 0.001), a finding that was similar for the composite cardiovascular outcome. Higher quartiles of 44hour-SBP-ARV were significantly associated with higher future risk for all studied outcomes. Among diastolic BPV indices, 44hour-DBP-CV and 44hour-DBP-ARV were associated with increased risk for the composite cardiovascular outcome. In Cox regression analysis all SBP-BPV indices were related to the primary end-point, independently of SBP levels (ARV: HR: 1.118, 95%CI: 1.055-1.185, per mmHg increase). Conclusions: Increased BPV during the interdialytic interval is associated with higher risk of death and cardiovascular events in hemodialysis, whereas ambulatory BP levels per se are not. Short-term BPV could be a major player promoting the adverse cardiovascular profile of these individuals.